Verification and validation for quality of UML 2.0 models - Unhelkar, Bhuvan (Hoboken, NJ : John Wiley, 2005)
A practical approach to enhancing quality in software models using UML Version 2.0"Despite its increasing usage, many companies are not taking the best advantage of UML and, occasionally, individuals have experienced frustration in applying its standards.
VERIFICATION AND VALIDATION FOR QUALITY OF UML 2.0 MODELS; Contents; Figures; Foreword; Preface; Acknowledgments; Glossary of Acronyms and Terms; Author Profile; 1 The Quality Strategy for UML; 2 Nature and Basics of UML Diagrams; 3 Strengths, Weaknesses, Objectives and Traps (SWOT) of UML Diagrams; 4 V & V of the Quality of MOPS; 5 V & V of the Quality of MOSS; 6 V & V of the Quality of MOBS; 7 Managing the V & V Process; Appendix A LUCKY Insurance Case Study; Appendix B UML CASE Tools; Appendix C Summary of Checks for V & V of the Quality of MOPS.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
John Wiley and Sons
Keywords: Computer software -- Verification; Computer software -- Quality control; UML (Computer science); Computer programs -- Verification; Logiciels; Logiciels -- x; UML (Informatique); COMPUTERS -- Software Development & Engineering -- Quality Assurance & Testing; Computer programs -- Verification; Computer software -- Quality control; Computer software -- Verification; UML (Computer science)